Reelin promotes oligodendrocyte precursors migration via the Wnt/β-catenin signaling pathway. (3rd July 2021) - Liu, Yaping; Wang, Yuanyuan; Yuan, Wen; Dong, Fuxing; Zhen, Fei; Liu, Jing; Yang, Lihua; Qu, Xuebin; Yao, Ruiqin
ABSTRACT: Objectives : The extracellular matrix glycoprotein Reelin plays an important role in the development of the central nervous system and is involved in neurogenesis, neuronal polarization and migration. Although it has been reported that Reelin and its receptor are expressed in oligodendrocyte precursors (OPCs), the main functions and possible mechanism of Reelin in OPCs remain unclear. Methods : In this study, immunofluorescence staining was used to detect the expressions of A2B5, PDGFRα, Reelin, VLDLR and Dab1 in OPCs. The expression of p-Dab1 in OPCs which was treated with Reelin at different concentrations was assayed by western blot. Effects of Reelin on the proliferation of OPCs was measured by EdU and CCK-8. Annexin V-FITC/PI assayed the effect of Reelin on the apoptosis of OPCs. Effects of Reelin on the migration ability of OPCs were detected by the scratch test and transwell experiments. Immunoblotting was used to measure the activation of Wnt/β-catenin signaling with Reelin, while transwell experiments were performed to verify the migration of OPCs under the activation of Wnt/β-catenin signaling. Results : Results showed that the receptor of Reelin, very-low-density lipoprotein receptor (VLDLR), and its adaptor protein, Dab1, are highly expressed in A2B5/PDGFRα double-positive OPCs. Recombinant Reelin protein promoted OPCs migration in vitro but had no obvious effects on proliferation or apoptosis. Reelin also promoted the phosphorylation of Dab1 and increased the expression of β-catenin in OPCs. WIKI4, an inhibitor of Wnt/β-catenin signaling, suppressed the migration of OPCs induced by Reelin. Conclusion : The present study indicated that Reelin promotes OPCs migration via the Wnt/β-catenin pathway.